Benchmarking Complications Associated with Esophagectomy. Issue 2 (February 2019) - Low, Donald E.; Kuppusamy, Madhan Kumar; Alderson, Derek; Cecconello, Ivan; Chang, Andrew C.; Darling, Gail; Davies, Andrew; D'Journo, Xavier Benoit; Gisbertz, Suzanne S.; Griffin, S. Michael; Hardwick, Richard; Hoelscher, Arnulf; et al.
Abstract : Objective: Utilizing a standardized dataset with specific definitions to prospectively collect international data to provide a benchmark for complications and outcomes associated with esophagectomy. Summary of Background Data: Outcome reporting in oncologic surgery has suffered from the lack of a standardized system for reporting operative results particularly complications. This is particularly the case for esophagectomy affecting the accuracy and relevance of international outcome assessments, clinical trial results, and quality improvement projects. Methods: The Esophageal Complications Consensus Group (ECCG) involving 24 high-volume esophageal surgical centers in 14 countries developed a standardized platform for recording complications and quality measures associated with esophagectomy. Using a secure online database (ESODATA.org), ECCG centers prospectively recorded data on all resections according to the ECCG platform from these centers over a 2-year period. Results: Between January 2015 and December 2016, 2704 resections were entered into the database. All demographic and follow-up data fields were 100% complete. The majority of operations were for cancer (95.6%) and typically located in the distal esophagus (56.2%). Some 1192 patients received neoadjuvant chemoradiation (46.1%) and 763 neoadjuvant chemotherapy (29.5%). Surgical approach involved open procedures in 52.1% and minimally invasive operations in 47.9%. Chest anastomoses were done most commonly (60.7%) and R0 resections were accomplished in 93.4% of patients. The overall incidence of complications was 59% with the most common individual complications being pneumonia (14.6%) and atrial dysrhythmia (14.5%). Anastomotic leak, conduit necrosis, chyle leaks, recurrent nerve injury occurred in 11.4%, 1.3%, 4.7%, and 4.2% of cases, respectively. Clavien-Dindo complications ≥ IIIb occurred in 17.2% of patients. Readmissions occurred in 11.2% of cases and 30- and 90-day mortality was 2.4% and 4.5%, respectively. Conclusion: Standardized methods provide contemporary international benchmarks for reporting outcomes after esophagectomy. Abstract : Supplemental Digital Content is available in the text